LIMITATION OF POPULATION EXPOSURE INDOORS DUE TO NATURAL IRRADIATION SOURCES: IAEA NEW SAFETY STANDARDS PROJECT - I. P. Stamat (Радиационная гигиена)
An article contains the analysis of the main expected changes in the setting standards of population exposure from natural sources in connection with the publication of the new IAEA standard «Protection of the Public against Exposure Indoors due to Natural Sources of Radiation».